The Polish Senate and the Armed Aggression of the Russian Federation on Ukraine - Okrzesik, Janusz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The paper explores activities undertaken by the Senate of the Republic of Poland in the early stages of full-scale armed Russian aggression on Ukraine. The activities of the Senate are analysed from a number of angles. Political positions and viewpoints expressed by the Senate as a whole are examined. Secondly, the participation of the Senate in the legislative procedure regarding help offered to Ukraine and Ukrainian citizens is discussed. Thirdly, the bilateral relations between the Polish Senate and the Verkhovna Rada of Ukraine are scrutinized and fourthly, individual activities of Tomasz Grodzki, the Marshal of the Senate, are looked upon. The Senate as a whole as well as its individual members showed a considerable level of commitment to the Ukrainian cause, however, the efficiency of undertaken steps was significantly hindered by the unequal position of the Senate against the Sejm and by the political conflict stirred by the fact that it is the opposition that enjoys the majority in the upper house of Polish parliament. Despite these unfavourable conditions, time and again, the efforts of the members of the Senate brought the expected results and considerably contributed to the shape of relevant legislation and to the development of Polish-Ukrainian relations.